Herding behavior analysis of Jakarta Islamic Index 2019-2024 - Delima, Bella; Sugianto, Sugianto; Bi Rahmani, Nur Ahmadi Bi Rahmani Ahmadi (LPMP Imperium, 2025)
The number of new investors on the Indonesia Stock Exchange has steadily increased in the past five years. However, both literacy and inclusion levels remain very low. This raises concerns about herding behavior in the stock market, leading to market prices not accurately reflecting true value. The author employs the CSAD method, utilizing variables such as market return (Rmt), CSAD, and Rm,t2, followed by a regression analysis. The data processing is carried out using EViews software, version 13, to enhance the accuracy and reliability of the research outcomes. The findings indicate significant herding activity among stocks indexed in the Indonesian JII from 2019 to 2024. From an Islamic perspective, natural herding behavior can be seen as a normal reaction due to market psychology. However, when herding is driven by deliberate manipulation—such as acts of Najsy or Ghisysy, which arise from misleading information, price manipulation, or non-transparent activities like pump and dump or hype and dump—it constitutes a violation of ethical standards and fair market principles, rendering it illegal. Public interest statements The findings emphasize the necessity for clear ethical guidelines for investors and market participants. Creating a code of conduct that prioritizes ethical trading practices can help reduce the risks tied to herding behavior and foster a fairer market environment. Note: Early Version articles are published as standalone pieces and will later be compiled into issues prior to print publication. These Early Version articles will not appear in journal keyword searches, will not be included in article searches, and will not receive a DOI (Digital Object Identifier) until they are officially published in an issue.